Mobility versus retention of mercury in bare and salt marsh sediments of a recovering coastal lagoon (Ria de Aveiro, Portugal). (October 2018) - Oliveira, Vitor H.; Coelho, J.P.; Reis, A.T.; Vale, C.; Bernardes, C.; Pereira, M.E.
Abstract: During decades, mercury (Hg) was discharged into the Aveiro Lagoon. Twenty-five years after the cessation of discharges, sediment cores were collected at two areas to assess the evolution of the mercury contamination status. Vertical Hg profiles differed considerably between bare and vegetated sediments. Bare sediments contained significantly less Hg (<8 mg kg −1 ) than historical data of 1995 (up to 40 mg kg −1 ), probably resulting from erosion. Salt marsh sediments were marked by a Hg sub-surface enrichment, reaching 44 mg kg −1 in the site closer to the industrial discharge point. High Hg concentrations in 2007, 2011 and 2016 were found at similar sediment layers. These results emphasise the role of halophyte plants in the cycling and retention of Hg in sediments. The persistency of high Hg in the upper marsh layers highlights the complexity in the recovery of historically contaminated marshes and the vulnerability to modifications in hydrology associated with climate changes. Highlights: Vertical Hg profiles differed considerably between bare and vegetated sediments. Mercury concentrations in bare-bottom sediments have reduced over time reflecting erosion and export of contaminant. Salt marsh sediments were marked by a Hg sub-surface enrichment, with similar concentration and depth from 2007 onwards. The persistency of Hg in the upper marsh layers highlights the complex recovery of historically contaminated marshes.